An Analysis of Adaptive Reasoning Ability in Middle School Students Mathematics Learning - Dela Amelia Putri; Attin Warmi (Jurnal Pendidikan Matematika (JPM), 2024)
Mathematics is one of the subjects taught in formal educational institutions, which is an important part of efforts to improve the quality of education. Students' adaptive reasoning ability in mathematics is reflected through their critical, logical, and systematic thinking, and their objective, honest, and disciplined nature in solving problems, whether in mathematics, other subjects, or daily life. This study aims to evaluate the adaptive reasoning ability in mathematics of middle school students. This research employs a qualitative approach with a descriptive method. The subjects of this study were 14 students from SMPIT Al-Irsyad Al-Islamiyyah Karawang, grouped into five levels: very high, high, medium, low, and very low. Data were collected from the tests on adaptive reasoning ability in mathematics to understand the students' reasoning abilities. Scores were given to students who answered each question based on the indicators achieved. The highest percentage was obtained on the indicator of forming conjectures, at 48.21%, while the lowest rate was 3.57% on the indicator of finding patterns in a mathematical phenomenon. Overall, the average results for each indicator were: Indicator 1 - 48.21%, Indicator 2 - 26.79%, Indicator 3 - 35.71%, Indicator 4 - 8.93%, and Indicator 5 - 3.57%. Therefore, the average percentage of student achievement in answering the adaptive reasoning ability test in mathematics was 24.64%. It can be concluded that middle school students' mastery of adaptive reasoning ability in mathematics is categorized as low.